Pengaruh Organizational Citizenship Behavior dan Kepuasan Kerja terhadap Kinerja Karyawan - Widiastuti, Ni Made Nindy; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
An organization will achieve its goals if its employees work well and perform optimistically. Organizational citizenship behavior (OCB) and job satisfaction are interesting aspects to study to measure employee performance in an organization and company. Quantitative measurement related to the impression of OCB and job satisfaction on employee performance is the main objective of this study. The study was conducted at the Bali Regional Settlement Infrastructure Center, with a sample of 137 employees. Data were collected using observation, interview, and questionnaire methods, with instruments that had been tested for validity and reliability. The data obtained were then analyzed using quantitative multiple linear regression analysis. The results of the study showed that there was a positive significance of the OBC variable and job satisfaction on employee performance. The findings were formulated in line with quantitative analysis evidence showing that all independent variables contributed positively and significantly to the independent variables, so that H1, H2, H3 were accepted.